Identification of putative genes for polyphenol biosynthesis in olive fruits and leaves using full-length transcriptome sequencing. (1st December 2019) - Guodong, Rao; Jianguo, Zhang; Xiaoxia, Liu; Ying, Luo
Highlights: Olive ( Olea europaea ) is a rich source of valuable bioactive polyphenols. Concentrations of 12 major polyphenols were measured. Both of second-generation RNA-seq and full-length transcriptome were used. 232 alternative splicing events were analyzed for the first time in olive. Abstract: Olive ( Olea europaea ) is a rich source of valuable bioactive polyphenols, which has attracted widespread interest. In this study, we combined targeted metabolome, Pacbio ISOseq transcriptome, and Illumina RNA-seq transcriptome to investigate the association between polyphenols and gene expression in the developing olive fruits and leaves. A total of 12 main polyphenols were measured, and 122 transcripts of 17 gene families, 101 transcripts of 9 gene families, and 106 transcripts of 6 gene families that encode for enzymes involved in flavonoid, oleuropein, and hydroxytyrosol biosynthesis were separately identified. Additionally, 232 alternative splicing events of 18 genes related to polyphenol synthesis were analyzed. This is the first time that the third generations of full-length transcriptome technology were used to study the gene expression pattern of olive fruits and leaves. The results of transcriptome combined with targeted metabolome can help us better understand the polyphenol biosynthesis pathways in the olive.